Systemic Resolvin E1 (RvE1) Treatment Does Not Ameliorate the Severity of Collagen-Induced Arthritis (CIA) in Mice: A Randomized, Prospective, and Controlled Proof of Concept Study - De Molon, Rafael Scaf [UNESP]; Thurlings, Rogier M.; Walgreen, Birgitte; Helsen, Monique M.; Van Der Kraan, Peter M.; Cirelli, Joni Augusto [UNESP]; Koenders, Marije I. (Hindawi, 2019)
Specialized proresolving mediators (SPRM), which arise from n-3 long-chain polyunsaturated fatty acids (n-3FA), promote resolution of inflammation and may help to prevent progression of an acute inflammatory response into chronic inflammation in patients with arthritis. Thus, this study is aimed at determining whether systemic RvE1 treatment reduces arthritis onset and severity in murine collagen-induced arthritis (CIA) and spontaneous cytokine production by human rheumatoid arthritis (RA) synovial explants. 10-week-old DBA1/J male mice were subjected to CIA and treated systemically with 0.1 μg RvE1, 1 μg RvE1, 5 mg/kg anti-TNF (positive control group), PBS (negative control group), or with a combination of 1 μg of RvE1 plus 5 mg/kg anti-TNF using prophylactic or therapeutic strategies. After CIA immunization, mice were treated twice a week by RvE1 or anti-TNF for 10 days. Arthritis development was assessed by visual scoring of paw swelling and histology of ankle joints. Moreover, human RA synovial explants were incubated with 1 nM, 10 nM, or 100 nM of RvE1, and cytokine levels (IL-1β, IL-6, IL-8, IL-10, INF-γ, and TNF-α) were measured using Luminex bead array. CIA triggered significant inflammation in the synovial cavity, proteoglycan loss, and cartilage and bone destruction in the ankle joints of mice. Prophylactic and therapeutic RvE1 regimens did not ameliorate CIA incidence and severity. Anti-TNF treatment significantly abrogated signs of joint inflammation, bone erosion, and proteoglycan depletion, but additional RvE1 treatment did not further reduce the anti-TNF-mediated suppression of the disease. Treatment with different concentrations of RvE1 did not decrease the expression of proinflammatory cytokines in human RA synovial explants in the studied conditions. Collectively, our findings demonstrated that RvE1 treatment was not an effective approach to treat CIA in DBA1/J mice in both prophylactic and therapeutic strategies. Furthermore, no effects were noticed when human synovial explants were incubated with different concentrations of RvE1.